Salary and non-salary factors motivating to work. The Case of a selected bank from Poland - Agnieszka JUDKOWIAK; Wiktoria WINKEL (Communications of International Proceedings, 2023)
The key concept shaping the direction of development of the banking industry is corporate sustainability. The implementation of the organization's economic, social, or ecological goals depends on the organization's employees and their appropriate motivation to work. Motivating employees is an inherent element of the employment relationship. It is important for both the employee and the employer. There are many factors influencing employee motivation to work, including wage and non-wage factors. The aim of the work was to empirically analyze and evaluate the incentive system operating in a selected bank. The research material was obtained by conducting surveys using a survey questionnaire. The research was conducted in 2023. According to the findings, the most motivating factors in the study group were pay factors, especially base salary, and bonuses. Other factors motivating work were non-wage, immaterial factors such as: stable employment, regulated working hours. The results of the analysis of the motivation system operating in a selected bank may constitute a contribution to further research and the basis for building an optimal system for motivating employees to work in financial institutions.
Keywords: motivation; remuneration; sustainable development; corporate sustainability